Lignocellulose-Adapted Endo-Cellulase Producing Streptomyces Strains for Bioconversion of Cellulose-Based Materials - Ventorino, Valeria; Ionata, Elena; Birolo, Leila; Montella, Salvatore; Marcolongo, Loredana; de Chiaro, Addolorata; Espresso, Francesco; Faraco, Vincenza; Pepe, Olimpia (Frontiers in Microbiology, 2016)
Twenty-four Actinobacteria strains, isolated from Arundo donax, Eucalyptus camaldulensis and Populus nigra biomass during natural biodegradation and with potential enzymatic activities specific for the degradation of lignocellulosic materials, were identified by a polyphasic approach. All strains belonged to the genus Streptomyces (S.) and in particular, the most highly represented species was Streptomyces argenteolus representing 50% of strains, while 8 strains were identified as Streptomyces flavogriseus (synonym S. flavovirens) and Streptomyces fimicarius (synonyms Streptomyces acrimycini, Streptomyces baarnensis, Streptomyces caviscabies, and Streptomyces flavofuscus), and the other four strains belonged to the species Streptomyces drozdowiczii, Streptomyces rubrogriseus, Streptomyces albolongus, and Streptomyces ambofaciens. Moreover, all Streptomyces strains, tested for endo and exo-cellulase, cellobiase, xylanase, pectinase, ligninase, peroxidase, and laccase activities using qualitative and semi-quantitative methods on solid growth medium, exhibited multiple enzymatic activities (from three to six). The 24 strains were further screened for endo-cellulase activity in liquid growth medium and the four best endo-cellulase producers (S. argenteolus AE58P, S. argenteolus AE710A, S. argenteolus AE82P, and S. argenteolus AP51A) were subjected to partial characterization and their enzymatic crude extracts adopted to perform saccharification experiments on A. donax pretreated biomass. The degree of cellulose and xylan hydrolysis was evaluated by determining the kinetics of glucose and xylose release during 72 h incubation at 50°C from the pretreated biomass in the presence of cellulose degrading enzymes (cellulase and β-glucosidase) and xylan related activities (xylanase and β-xylosidase). The experiments were carried out utilizing the endo-cellulase activities from the selected S. argenteolus strains supplemented with commercial β-gucosidase and xylanase preparations from Genencore (Accellerase BG and Accellerase XY). Cellulose and xylan conversion, when conducted using commercial (hemi)cellulases, gave glucose and xylose yields of 30.17 and 68.9%, respectively. The replacement of the cellulolytic preparation from Genencor (Accellerase 1500), with the endo-cellulase from S. argenteolus AE58P resulted in almost 76% of the glucose yield obtained in the presence of the commercial counterpart. Due to the promising results obtained by using the enzymatic crude extracts from S. argenteolus AE58P in the pretreated A. donax saccharification experiments, the proteins putatively responsible for endo-cellulase activity in this strain were identified by proteomics. Several proteins were confidently identified in different Streptomyces spp., eight of which belong to the class of Carbohydrate active enzymes. Overall results highlighted the biotechnological potential of S. argenteolus AE58P being an interesting candidate biocatalyst-producing bacterium for lignocellulose conversion and production of biochemicals and bioenergy.